PERSEPSI ORANGTUA TERHADAP ANAK-ANAK PENGGUNA MEDIA SOSIAL TIKTOK - Hardian Mulya; Tessa Shasrini (Yayasan Nusantara Hasana Berdikari, 2023)
This study aims to find out how parent’s perceive their children using TikTok social media who take a case study in RT 002 RW 003 Kampung Baru ward Senapelan District, Pekanbaru, Riau. the smartphone, and what if to access various videos in the video-sharing-based social media application that the researcher is currently taking, namely TikTok. in the form of descriptive sentences that describe the entire contents of this study. The data collection methods are in-depth interviews, research photos, voice recordings, and descriptive questionnaires which the researchers distributed via the google form link. This research that takes perception theory by Brian Fellows has 2 types of perceptions which are grouped into positive and negative. Such as TikTok as a source of information and adding insight, TikTok as a place to hone creativity, and TikTok as a self-confidence maker for the positive side, then the negative is TikTok as a presenter of entertainment that often makes children neglect, TikTok as a generation that likes to dance with unconventional movements. profanity, TikTok which gives an addictive effect and serious effects on health and TikTok as the cause of the tendency of people to do things based on what is trending on their FYP (for your page)